Predicting the effectiveness of omalizumab in patients with refractory chronic rhinosinusitis with nasal polyps comorbid with asthma based on inflammatory biomarkers - Yutong Sima, MD; Ming Zheng, MD; Yan Zhao, PhD; Siqi Ge, PhD; Chengyao Liu, MD; Ping Wang, BS; Xiangdong Wang, MD, PhD; Luo Zhang, MD, PhD (World Allergy Organization Journal)
Background: The treatment of refractory chronic rhinosinusitis with nasal polyps (CRSwNP) with omalizumab has been well studied based on clinical evaluation. Nevertheless, ideal quantitative or qualitative biomarkers for predicting a different response to biologics urgently need to be explored. We aim to identify potential biomarkers for predicting a good or poor response in patients with refractory CRSwNP. Methodology: Patients received an endoscopic and radiological evaluation, a visual analogue scale (VAS) assessment, and a 22-item sinonasal outcome test (SNOT-22). Forty-eight biomarkers involving type 1 (T1), type 2 (T2), and type 3 (T3) inflammatory factors, chemokines, and remodeling factors were detected in nasal secretion and serum samples at baseline and after 24 weeks of omalizumab treatment. Results: Eighteen patients with CRSwNP and 16 patients as control were enrolled. Patients with CRSwNP who received oamlizumab treatment with the SNOT-22 and VAS scores improved by 8.9 and 2 points in 72.22% and 50%, respectively. The nasal polyp score (NPS) and Lund-Mackay score were significantly improved in 55.56% of patients. The concentrations of T2 inflammatory biomarker, granulocyte-macrophage colony-stimulating factor (GM-CSF), T3 inflammatory biomarkers, granulocyte colony-stimulating factor (G-CSF), chemokine (C-X-C motif) ligand (CXCL)-1, and chemokine (C–C motif) ligand-20 (CCL-20), T1 inflammatory biomarker, IP-10 (CXCL-10), and granzyme B in nasal secretion and serum periostin were significantly decreased. Serum CCL-3 (AUC = 0.836) and CCL-4 (AUC = 0.909) levels predicted the improvement of SNOT-22 score, respectively. Serum IL-8 (AUC = 0.883) predicted poor improvement in nasal congestion score. Nasal secretion CXCL-1 (AUC = 0.812), GM-CSF (AUC = 0.813), IgE (AUC = 0.900) and IP-10 (AUC = 0.800) effectively predicted none or less improvement in nasal polyp score. Conclusions: Omalizumab remarkably affects inflammatory mediators in different pathways. CCL-3 and CCL-4 in serum and IgE, CXCL-1, GM-CSF, and IP-10 in nasal secretion may be considered as preferable biomarkers for predicting favorable or ineffective response to omalizumab therapy in patients with refractory CRSwNP comorbid with asthma, based on various clinical indicators.